Abundance of Aphis gossypii (Homoptera; Aphididae) and its main predators in organic and conventional cotton fields in north‐west China. (18th December 2014) - Lu, Z‐Z.; Perkins, L.E.; Li, J‐B.; Wu, W‐Y.; Zalucki, M.P.; Gao, G‐Z.; Furlong, M.J.
Abstract Understanding how natural assemblages of predators are affected by organic agriculture, and whether these changes can contribute to biological control, is important for the design of Integrated Pest Management (IPM) strategies and sustainable agriculture. The effect of organic management practices on the abundance of the cotton aphid Aphis gossypii and its major predators was evaluated in northwestern China during the cotton‐growing seasons of 2004–2006. The predators of A. gossypii in cotton fields included Coccinellidae (ladybirds), Chrysopidae (lacewings), spiders (Linyphiidae and Thomisidae) and Syrphidae (hoverflies). Higher peak densities and longer persistence of predators in organic fields were found, and the average annual densities of all predators except Chrysopidae adults were higher, on average by 200%, in organic fields than in conventional fields in all 3 years. The abundance of larvae of Coccinellidae, Chrysopidae and Syrphidae was higher in organically managed crops indicating that these predators bred more successfully in organic fields. Although there was a significant difference between A. gossypii abundance in organic and conventional fields each year, taken over the three‐year period as a whole there was no significant difference. This suggests predation by natural enemies in organic fields can achieve the same efficacy in aphid control as pesticides used in conventional fields over the long term, but that predation does not prevent outbreaks of A. gossypii in some years.